GLOBAL ECONOMIC CHALLENGES IN CONDITIONS OF FINANCE CRISIS - Evgeniy V. Afanasyev; Ivan P. Ivanov (Вестник Российского экономического университета имени Г. В. Плеханова)
The article discusses global economic problems in conditions of finance crisis from the point of view of market economy development. The development of humanity today has mainly the economic component and business processes in conditions of market economy are considered only in view of profit. According to the author it is groundless, as economic processes apart from economic components must bear social and humanitarian function. Only in this situation science starts working for society but not for a small group or several groups , who lobby their own targets and interests. Main problems in the dynamic of global social and economic processes and growth in confrontation of interests of different public groups are identified as the movement of two interconnected powers, i.e. collective labor and private capital, in different directions and their inversely proportional accumulation of capital.